THE EFFECTIVENESS OF LEARNING DEVICE BASED ON SCIENCE, TECHNOLOGY, SOCIETY, AND ENVIRONMENT (STSE) TO IMPROVE STUDENTS SCIENTIFIC LITERACY - Nughraha, Hafizhah Sri (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This research was motivated by the low level of students' scientific literacy due to the lack of learning device designed to train students' scientific literacy. This research aimed to determine the effectiveness of learning devices based on Science, Technology, Society, and Environment (STSE) on biotechnology material which was feasible to improve students' scientific literacy. The learning device which was developed consisted of syllabus, learning implementation plan (RPP), student book, student workheets (LKPD), and learning result test instrument. The developed learning device was implemented to three classes of VIII grade students of SMPN 1 Campurdarat Kabupaten Tulungagung in Second Semester in 2017/2018 Academic Year. The result of this research was level of students' scientific literacy reached level 1b to 3 in pretest and reached level 2 to 5 in posttest. Based on the analysis of research results and discussion, it could be concluded that the learning device based on Science, Technology, Society, and Environment (STSE) was effective to improve students' scientific literacy.